Facial paralysis induced by ear inoculation of herpes simplex virus in rat. Issue 1 (February 2017) - Fujiwara, Takashi; Matsuda, Seiji; Tanaka, Junya; Hato, Naohito
Abstract: Objective: Bell's palsy is caused by the reactivation of herpes simplex virus type 1 (HSV-1). Using Balb/c mice inoculated with the KOS strain of HSV-1, we previously developed an animal disease model that simulated mild Bell's palsy. The current study developed an animal disease model of more severe facial palsy than that seen in the mouse model. Methods: Three-week-old female Wister rats weighing 60–80 g were inoculated on the auricle with HSV-1 and acyclovir was administered intraperitoneally to deactivate the infected HSV-1. Instead of HSV-1, phosphate-buffered saline was used for inoculation as a negative control. Quantitative polymerase chain reaction (PCR), behavior testing (blink reflex), electroneuronography, histopathology of the peripheral nerve, and immunohistochemistry of the facial nerve nucleus were evaluated. Results: Facial palsy occurred 3–5 days after virus inoculation, and the severity of the facial palsy progressed for up to 7 days. Quantitative PCR showed an increase in HSV-1 DNA copies in the facial nerve from 24 to 72 h, suggesting that HSV-1 infection occurred in the nerve. Electroneuronography values were 33.0 ± 15.3% and 110.0 ± 18.0% in HSV-1-inoculated and control rats, respectively. The histopathology of the peripheral nerve showed demyelination and loss of the facial nerve, and the facial nerve nucleus showed degeneration. Conclusion: Facial palsy developed in Wister rats following inoculation of the KOS strain of HSV-1 onto the auricles. The behavioral, histopathological, and electroneuronography data suggested that the severity of facial palsy was greater in our rats than in animals in the previous mouse disease model.